209k views
2 votes
Rearrange the formula a^2 + b^2 = c^2 for a.

User LemonCool
by
6.4k points

2 Answers

4 votes

First, subtract the term b^2 from the both sides of the equation to isolate a^2. Then, take the square root of both sides of the equation so "a" is completely isolated. And voila! You should have the simplified version of this formula.

User Ihsanullah Khan
by
5.4k points
2 votes
We were given


a^2 +b^2 = c^2

Adding
b^2 to both sides of the equation gives,


a^2=c^2-b^2

The Right Hand Side of the equation is a difference of two squares. So we can factor it as follows:


a^2= (c+b)(c-b)

Taking the square root of both sides we have,


a=\sqrt((c+b)(c-b))